Komunikasi Pembangunan dalam Pengendalian Rabies di Kota Pekanbaru - Ammalia Retno Sari; Mayarni Mayarni (Badan Penerbit STIEPARI Press, 2026)
This study discusses efforts to control rabies in Pekanbaru City. Rabies is a dangerous and deadly zoonotic disease that is still rampant in Pekanbaru City. The reason why there are still many cases of rabies in Pekanbaru City is duet o the coverage rabies transmitting animals (RTA) vaccination has not reached the target ≥70% according to the Regulation Minister of Agriculture Number 39 of 2023 concerning Minimum Priority Zoonosis Services and The Lack of Public Awareness in preventing rabies is the background to this research. This study aims to determine the development communication process that carried out by the Pekanbaru City Agriculture and Fisheries Service in an effort to control rabies and identify the inhibiting factors of development communication. Techniques data collection was conducted through in-depth interviews, observation, and documentation. Results research shows that development communication in rabies control has implementations through Communication, Information and Education (KIE) activities but not yet running optimally. The inhibiting factors found include mechanical obstacles, namely limitations of media for conveying information, cultural barriers in the form of still being found people who consume rabies transmitting animals (RTA) such as dogs have bad impact on their health, and behavioral barriers in the form of public perception that vaccination is not important. Comprehensive communication efforts are required, implementation of appropriate programs that have been implemented established, and community participation to increase awareness in controlling rabies.